"SHOUT" to improve the quality of care delivered to patients with acute kidney injury at Great Western Hospital. Issue 1 (18th November 2015) - Brady, Paul; Gorham, James; Kosti, Angeliki; Seligman, William; Courtney, Alona; Mazan, Karolina; Paterson, Stuart; Ramcharitar, Steve; Chandrasekaran, Badri; Juniper, Mark; Greamspet, Mala; Daniel, Jessica; et al.
Abstract: Acute kidney injury (AKI) affects up to 20% of all patients admitted to hospital, and is associated with a higher risk of adverse clinical outcomes, increased healthcare costs, as well as long term risks of chronic kidney disease and end stage renal failure. The aim of this project was to improve the quality of care for patients with AKI admitted to the acute medical unit (AMU) at the Great Western Hospital (GWH). We assessed awareness and self reported confidence among physicians in our Trust, in addition to basic aspects of care relevant to AKI on our AMU. A multifaceted quality improvement strategy was developed, which included measures to improve awareness such as a Trust wide AKI awareness day, and reconfiguring the admission proforma on our AMU in order to enhance risk assessment, staging, and early response to AKI. Ancillary measures such as the dissemination of flashcards for lanyards containing core information were also used. Follow up assessments showed that foundation year one (FY1) doctors' self reported confidence in managing AKI increased from 2.8 to 4.2, as measured on a five point Likert scale (P=0.0003). AKI risk assessment increased from 13% to 57% (P=0.07) following a change in the admission proforma. Documentation of the diagnosis of AKI increased from 66% to 95% (P=0.038) among flagged patients. Documentation of urine dip results increased from 33% to 73% (P=0.01), in addition to a rise in appropriate referral for specialist input, although this was not statistically significant. Our results suggest that using the twin approaches of improving awareness, and small changes to systemic factors such as modification of the admission proforma, can lead to significant enhancements in the quality of care of patients with AKI.